2017
DOI: 10.1080/14670100.2017.1341362
|View full text |Cite
|
Sign up to set email alerts
|

The impact of vestibular status prior to cochlear implantation on postural control: A multiple case study

Abstract: A thorough evaluation of the vestibular function, as described in the present study, could not only be helpful to make a more accurate prognosis of the risks of fall following cochlear implantation, but also to provide proper vestibular rehabilitation for at-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
6
0
1
Order By: Relevance
“…Regarding the general characteristics of the articles included in the systematic review, 6 articles carried out their research using a control group compared to those implanted ( 23 , 34 , 41 , 42 , 49 ), while the remaining 32 studies compared the results of their patients before and after cochlear implant ( Supplementary Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the general characteristics of the articles included in the systematic review, 6 articles carried out their research using a control group compared to those implanted ( 23 , 34 , 41 , 42 , 49 ), while the remaining 32 studies compared the results of their patients before and after cochlear implant ( Supplementary Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Among all the 38 articles, after judgment based on the risk of bias analysis (JBI), analytic cross-sectional studies, and according to each study type, 25 studies showed a low risk of bias ( 9 , 14 , 16 , 24 , 27 , 31 , 33 , 35 , 36 , 38 , 39 , 42 44 , 46 , 48 55 ), 10 articles ( 15 , 23 , 25 , 26 , 28 30 , 32 , 34 , 47 ) showed a moderate risk of bias, and 3 articles ( 21 , 40 , 45 ) had a high risk of bias.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of preliminary examination before cochlear implantation, cochlear diagnostics are recommended in order to obtain basic information about the peripheral vestibular function. Sometimes, also a prognostic statement about the risk of vestibular damage associated with cochlear implantation seems to be possible [50]. Due to regularly performed vestibular diagnostics, it is possible to inform and consult in an optimized way regarding the risk of vestibular damage associated with cochlear implantation [50].…”
Section: Assessment Of the Vestibular Diagnosticsmentioning
confidence: 99%
“…Sometimes, also a prognostic statement about the risk of vestibular damage associated with cochlear implantation seems to be possible [50]. Due to regularly performed vestibular diagnostics, it is possible to inform and consult in an optimized way regarding the risk of vestibular damage associated with cochlear implantation [50]. Furthermore, a vestibular test that reveals pathologic side differences may also support the decision of which side should be implanted [51].…”
Section: Assessment Of the Vestibular Diagnosticsmentioning
confidence: 99%